Combined effect of carvacrol and high hydrostatic pressure on quality attributes of chicken meat during refrigerated conditions - Hussein, Khabat Noori; Csurka, Tamás; Meena, Bashdar I.; Ahmed, Hiwa M.; Varga-Tóth, Adrienn; Hidas, Karina; Gábor, Jónás; Németh, Csaba; Friedrich, László; Dalmadi, István (Emirates Journal of Food and Agriculture, 2023)
The application of hurdle approach using high hydrostatic processing (HHP) with bioactive compounds (BACs) to preserve meat quality is promising due to safety, improved well-being, and easier acceptance by customers compared to the use of synthetic preservatives. This study was designed to investigate the influence of natural phenolic BAC carvacrol (CARV) at 500 and 1000 ppm combined with HHP(300 and 600MPa) on the quality attributes of chicken meat after being vacuum-sealed and kept at 4 ± 0.5 °C for 28 days. The HHP showed a significantly higher pH rate (P<0.05), increased L* and b* value, decreased a* values, and reduction in water holding capacity (WHC) compared to unpressurized control meat with/without CARV. Reduction in thiobarbituric acid reactive substances (TBARS) indexes was perceived in meat supplemented with CARV, and low level of HHP (300 HHP) whereas significantly increased lipid oxidation was witnessed with HHP 600 MPa. At day 28, an increase in aerobic mesophilic counts (AMCs) was observed in all meat samples. However, reductions of about 0.6, 0.8, and 1.1 log in AMCs were seen in meat treated with 600HHP-No CARV, HHP300-CARV 500 ppm, and 600HHP-CARV 1000 ppm, respectively. Furthermore, despite the overlapping aroma pattern between meat containing CARV and control groups, the electronic nose was able to discriminate control from samples subjected to HHP. The current results demonstrate that the addition of CARV improved the conservation effects of HHP with less oxidative deterioration of fresh chicken meat during chilling storage. Keywords: Bioactive compounds; High hydrostatic processing; Chicken meat; Lipid oxidation; Microbiological properties